Bates and Olmstead: Court-initiated Strategies to Implement Community Inclusion of Persons with Psychiatric and Other Long-term Disabilities - Laurie, Theresa (Maine Policy Review, 2004)
In this commentary, Theresa Laurie discusses the impact of the Bates and Olmstead court decisions regarding the rights of the disabled, and their applicability to people with psychiatric and other long-term disabilities. She notes that Maine will have to make policy adjustments in order to redefine program objectives based on these court decisions.